The Relationship Between Milk Bottle Hygiene and the Incidence of Diarrhea in Infants Aged 0-6 Months: A Study in Gajahan Health Center, Surakarta - Aisya Fikritama Aditya; Putri Riyan Handrajati; Pitra Sekarhandini (Asosiasi Dosen Muda Indonesia, 2026)
Diarrheal disease remains a significant cause of infant morbidity and mortality worldwide, particularly in developing countries like Indonesia. This study examines the relationship between milk bottle hygiene and the incidence of diarrhea in infants aged 0-6 months in Surakarta, Indonesia, with the goal of highlighting the importance of proper bottle sanitation in reducing diarrhea risk. Objective: The objective of this study is to analyze the relationship between milk bottle hygiene and the incidence of diarrhea in infants aged 0-6 months. The study aims to provide insights into the role of bottle sanitation in preventing gastrointestinal infections in infants. Methodology: This research employed a quantitative, analytic observational approach using a cross-sectional study design. The population consisted of 50 infants who met specific inclusion and exclusion criteria. Data were collected through structured questionnaires, and chi-square tests were used for statistical analysis to assess the relationship between milk bottle hygiene and diarrhea incidence. Findings: The study found a significant relationship between poor milk bottle hygiene and an increased incidence of diarrhea in infants (p-value < 0.05). The findings indicate that inadequate bottle cleaning practices contribute to gastrointestinal infections in infants, reinforcing the importance of proper hygiene in preventing diarrhea. Implications: The findings highlight the need for targeted public health interventions to educate mothers and caregivers on proper milk bottle sanitation. Implementing simple hygiene practices could significantly reduce the risk of diarrhea and other preventable gastrointestinal diseases in infants, particularly in resource-limited settings. Originality: This study offers original contributions by focusing on milk bottle hygiene as a key factor influencing diarrhea incidence in infants, an area that has been largely underexplored in previous research. The study provides valuable insights that could inform policies and interventions aimed at improving infant health and preventing diarrheal diseases.